Fundamentals and applications of modern flow control - Joslin, R. D. 1963-; Miller, Daniel N. (American Institute of Aeronautics and Astronautics, 2009)
Flow control technologies have been used in the past century to control fluid flows. This text presents the current state-of-the art in emerging modern flow control technologies and highlights the application of these technologies to aerospace platforms. Initial chapters introduce the fundamentals of modern flow control, including basic concepts, terminology, history, flow physics, actuators, sensors, modeling/simulation, and instability and control theories. Applications of flow control to current and next-generation air vehicle systems, including fixed wing airfoils, turbomachinery, combustion, aeroacoustics, vehicle propulsion integration, and rotorcraft are discussed. This text is an excellent introduction to the wide-ranging uses of modern flow control.